An impact analysis of the implementation of health technology assessment for new treatment of orphan diseases in Japan. (2nd September 2020) - Kogushi, Kentaro; Ogawa, Toshio; Ikeda, Shunya
ABSTRACT: Objectives : In Japan, a cost-effectiveness evaluation (CEE) for pricing was introduced in April 2019 and potentially covers orphan drugs (ODs) within its scope. The purpose of this study was to explore a reasonable approach to evaluate the utility of health technology assessment (HTA) for ODs in Japan. Methods : We extracted ODs that were approved in Japan from 2009 to 2018, and investigated their appraisals in the United Kingdom, Canada, and Australia, where HTA and different frameworks on ODs have been implemented. Results : Overall, 76 ODs were identified, with high recommendation rates in the three countries (80.6%-90.9%). The major reason for negative recommendation was uncertainty regarding clinical effectiveness, with actual decisions varying across countries. This indicates difficulties in setting an objective evaluation for the uncertainty of clinical effectiveness. The results of the CEE were mainly used to adjust prices. Conclusion : As Japan's CEE is expected to be used only for price adjustment after reimbursement is secured, the approach seems to be similar to the other countries. However, pre-launch clinical data are limited and the peak sales of ODs vary in Japan. Therefore, the careful introduction of CEE and multifaceted measures referring to the policies for ODs in other countries should be considered.